The impact of biomembranes and their dynamics on organismic aging: insights from a fungal aging model - Osiewacz, Heinz D. (Frontiers in Aging, 2024)
Biomembranes fulfil a number of essential functions. They delimitate cells, control the exchange of compounds between cells and with the environment. They generate specialized cellular reaction spaces, house functional units such as the respiratory chain (RC), and are involved in content trafficking. Biomembranes are dynamic and able to adjust their properties to changing conditions and requirements. An example is the inner mitochondrial membrane (IMM) which houses the respiratory chain (RC) involved in the formation of adenosine triphosphate (ATP) and the superoxide anion as a reactive oxygen species (ROS). The IMM forms a characteristic ultrastructure which can adapt to changing physiological situations. In the fungal aging model Podospora anserina, characteristic age-related changes of the mitochondrial ultrastructure occur. More recently, the impact of membranes on aging was extended to membranes involved in autophagy, an important pathway involved in cellular quality control (QC). Moreover, the effect of oleic acid on lifespan was linked to basic biochemical processes and the function of membranes providing perspectives for the elucidation of mechanistic effects of this nutritional component which positively effects human health and aging.